The evolution of green finance research: A comprehensive bibliometric analysis - Guizhou Wang; Hongrui Cui; Kjell Hausken (Heliyon)
The article investigates the evolution of green finance research through bibliometrics using 1923 publications from the Web of Science. It identifies key contributors, influential publications, and collaboration networks, while revealing three distinct research stages: (1) carbon finance and markets (2008–2010), (2) climate finance, climate policy, and climate change (2011–2017), and (3) sustainable development goals and financial development (2018–2022). Emerging topics such as green energy, green technology, carbon emissions, and the digital economy are highlighted. The result emphasizes the interdisciplinary nature of green finance, intersecting with environmental science, economics, and technology. The increasing publication and citation trends post-2019 reflect the growing importance of green finance in addressing global sustainability challenges. The findings offer valuable insights for researchers, policymakers, and practitioners, helping to identify knowledge gaps and future directions in green finance.